Implementation of Interactive Learning Strategies in Enhancing the Dynamics of Islamic Education Learning at MAS Tarbiyah Islamiyah Hamparan Perak - Zainuddin Zainuddin; Arya Pradana Sinaga; Mhd Isacc Kurniawan (Integrasi: Jurnal Studi Islam dan Humaniora, 2026)
This study aims to analyze the implementation of interactive learning strategies in improving the dynamics of Islamic Education learning at MAS Tarbiyah Islamiyah Hamparan Perak. This research employed a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation. The research informants consisted of the principal, Islamic Education teachers, and students. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The findings revealed that the implementation of interactive learning strategies was able to increase students’ involvement in the learning process, create an active and communicative learning atmosphere, and improve students’ motivation and understanding of Islamic Education materials. The strategies implemented included group discussions, question-and-answer sessions, presentations, and the use of interactive learning media. In addition, teachers acted as facilitators who encouraged students to think critically and collaborate during the learning process. Therefore, interactive learning strategies contributed positively to enhancing the dynamics of Islamic Education learning at MAS Tarbiyah Islamiyah Hamparan Perak.